Exosomes: The role in mammalian reproductive regulation and pregnancy-related diseases - Guo, Xing-Ru; Ma, Yun; Ma, Zi-Ming; Dai, Tian-Shu; Wei, Shi-Hao; Chu, Yuan-Kui; Dan, Xin-Gang (Frontiers in Physiology, 2023)
Exosomes are a kind of extracellular vesicles that are produced and secreted by different mammalian cells. They serve as cargo proteins and can transfer different kinds of biomolecules, including proteins, lipids, and nucleic acids, which consequently act on target cells to exert different biological effects. Recent years have witnessed a significant increase in the number of studies on exosomes due to the potential effects of exosomes in the diagnosis and treatment of cancers, neurodegenerative diseases, and immune disorders. Previous studies have demonstrated that exosomal contents, especially miRNAs, are implicated in numerous physiological processes such as reproduction, and are crucial regulators of mammalian reproduction and pregnancy-related diseases. Here, we describe the origin, composition, and intercellular communication of exosomes, and discuss their functions in follicular development, early embryonic development, embryonic implantation, male reproduction and development of pregnancy-related diseases in humans and animals. We believe this study will provide a foundation for revealing the mechanism of exosomes in regulating mammalian reproduction, and providing new approaches and ideas for the diagnosis and treatment of pregnancy-related diseases.